Politization of Local Government Budget Allocations in 2017 Election - Widawati, Mega Wahyu; Widagdo, Ari Kuncara (Universitas Pendidikan Indonesia, 2020)
This paper discusses about the election of regional heads to the regional government budget allocation. This study discusses the regional budget in the period before local election and during the local election. Comparison is done by comparing the average expenditure comparison before and during the local election period by using paired sample t-test. The sample in this study in Indonesia carried out the post-conflict local election in 2017. The results of this study showed that basically before the post-conflict local election and at the post-conflict local election. There was a decrease in the allocation of grant spending during the post-conflict local election compared to the previous year. Besides that, there was no difference in the allocation of social assistance expenditure. This can improve the renewal and regulatory system in Indonesia, thus indicating that budget politicization is not proven.